Meaning and Practice of Environmental Hygiene in Preventing Skin Diseases in Toddlers in the Service Area of Sabirabad Rayon Polyclinic - Charles Ayodeji Osunla; Taisia Chertenko (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aimed to explore the meaning and daily practice of environmental hygiene in preventing infectious skin diseases among toddlers in the service area of Sabirabad Rayon Polyclinic. Methodology: A qualitative descriptive–exploratory design was employed. Data were collected through in-depth interviews with 10 mothers or primary caregivers of toddlers who had experienced infectious skin conditions within the past six months. Participants were selected using purposive sampling. Data were analyzed using the interactive model of Matthew B. Miles and A. Michael Huberman, involving data reduction, data display, and conclusion drawing. Main Findings: All participants (100%) emphasized the importance of environmental cleanliness for child health; however, cleanliness was predominantly defined in terms of visible order rather than microbial risk prevention. Daily hygiene practices such as sweeping and bathing children were routinely performed, yet recurrent skin infections were reported by most caregivers, particularly during hot seasons. Barriers included limited water access, housing density, and financial constraints. Novelty/Originality of this study: This study shifts the analytical focus from measurable environmental risk factors to the socially constructed meanings of cleanliness and maternal responsibility, providing a culturally grounded perspective on hygiene behavior and skin disease prevention in primary care settings.